Ecocide: The Opportunity to be Included Globally, but also in National Laws - Pirvu, Loredana (Acta Universitatis Danubius. Juridica, 2025)
Humanity is facing major existential challenges, climate change and armed conflict are amplifying these pressures. The recognition of ecocide as a global crime is an important and current discussion. There is growing confidence in scientific evidence suggesting that the Earth has reached a “tipping point” (University of California – Berkeley, 2012) and is approaching “planetary limits” (Stockholm Resilience Centre, 2009) and the changes that are happening (climate change, population growth, destruction of natural ecosystems, warming of the oceans and melting of ice caps, massive increase in carbon pollution) they can be irreversible if we do not stop this decline (which began with the industrial revolution) before we reach the abyss. And we can stop it by certain measures that require large-scale international cooperation and the creation of the crime of ecocide is an important part of this sum of measures. The recognition of ecocide in national legislation is an important opportunity to combat environmental destruction and promote sustainability and can be a powerful tool for environmental protection, but its effectiveness depends on clarity of definition and uniform application. A unitary international framework, possibly through the International Criminal Court, would ensure consistency and efficiency in combating the worst environmental crimes.